2004
DOI: 10.1088/0953-8984/16/28/018
|View full text |Cite
|
Sign up to set email alerts
|

Fabrications and electrical properties of ferroelectric Bi3.25La0.75Ti3O12thin films using a indium–tin-oxide conductive layer as the bottom electrode

Abstract: Systematic effort was made to optimize the quality of ferroelectric Bi3.25La0.75Ti3O12 thin films, that were pulsed laser deposited onto indium–tin-oxide coated glass plates, by varying the conditions of laser fluence density, partial oxygen pressure and post-annealing temperature. Characterizations from the dielectric and ferroelectric measurements concluded that the films deposited with a laser power of 2.5 J cm−2, a deposition pressure of 200 mTorr and an annealing temperature of 650 °C showed the finest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The peak temperature of the dielectric spectrum corresponded to the ferroelectric-paraelectric phase transition temperature, i.e., the Curie temperature (T c ), as shown in the interpolation of Figure 4. The Curie temperatures of the pure BLT, Co-BLT, and FeCo-BLT ceramics were 400, 500, and 600 • C, respectively, at a frequency of 10 kHz; the T c of pure BLT corresponded to that of pure BLT in previous studies [22,23]. The BLT/FeCo-BLT and Co-BLT/FeCo-BLT composite films had ferroelectric temperatures of 650 • C and 700 • C, respectively, which were significantly higher than that of the base target.…”
Section: Resultsmentioning
confidence: 69%
“…The peak temperature of the dielectric spectrum corresponded to the ferroelectric-paraelectric phase transition temperature, i.e., the Curie temperature (T c ), as shown in the interpolation of Figure 4. The Curie temperatures of the pure BLT, Co-BLT, and FeCo-BLT ceramics were 400, 500, and 600 • C, respectively, at a frequency of 10 kHz; the T c of pure BLT corresponded to that of pure BLT in previous studies [22,23]. The BLT/FeCo-BLT and Co-BLT/FeCo-BLT composite films had ferroelectric temperatures of 650 • C and 700 • C, respectively, which were significantly higher than that of the base target.…”
Section: Resultsmentioning
confidence: 69%
“…The authors suggested that the hysteresis loop is rather shifted to the positive electric field as electrons from the ITO electrodes have been transported to the ferroelectric material under numerous switching cycles [9]. However, progress is still ongoing to understand the electrical characterizations of BLT thin film capacitors on other types of metallic oxide electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent schemes for reducing fatigue-related problems in PZT capacitors are replacing Pt electrodes with metallic oxide electrodes [6][7][8]. Because these oxide electrodes are electrically leaky and make the fabrication process more complicated and expensive, they are inappropriate to be used in applications [9].…”
Section: Introductionmentioning
confidence: 99%